Casting resin, shaped bodies produced therefrom and use of shaped bodies

By reducing the toughening agent in the casting resin and combining diglycidyl ether epoxy resin with alicyclic epoxy resin, polymer nanoparticles are solved, and the problem of difficult to take into account in the prior art materials' brittleness and fracture toughness is achieved. High glass transition temperature and crack resistance, suitable for high temperature electrical components manufacturing.

CN113924328BActive Publication Date: 2025-01-17SIEMENS AG

Patent Information

Application Number
CN202080039003.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-27
Filing Date
2020-03-09
Publication Date
2025-01-17
Estimated Expiration
2040-03-09

AI Technical Summary

Technical Problem

The existing casting resins for electrical potting are difficult to take into account while increasing the glass transition temperature, which leads to dimensional instability of the material and mechanical aging at high temperatures, affecting the reliability of electrical components.

Method used

By reducing or eliminating toughening agents in the casting resin, combining diglycidyl ether epoxy resin with alicyclic epoxy resin, and introducing highly dispersed polymer nanoparticles, increasing the glass transition temperature while maintaining the material processability and mechanical properties of fracture.

Benefits of technology

It achieves the improvement of the crack resistance and fracture toughness of the material without reducing the glass transition temperature, extending the service life of the material, and is suitable for the manufacturing of electrical components in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003374853330000091
    Figure BDA0003374853330000091
Patent Text Reader

Abstract

The invention relates to novel casting resin compositions and their use in heat-curing electrical potting, which is used, for example, in the production of electrical components such as transformers, insulators, capacitors, coils and assemblies. The invention also relates to shaped bodies obtainable from the casting resins, and to the use of such shaped bodies. The invention proposes for the first time a casting resin for heat-curing electrical encapsulation, in which plasticizers and toughening agents can be omitted. This is achieved by mixing an epoxy resin base with a cycloaliphatic epoxy resin and adding highly dispersed nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to novel casting resin compositions and their use in heat-cured electrical potting, which is used, for example, in the manufacture of electrical components such as transformers, insulators, capacitors, coils and assemblies. The invention also relates to shaped bodies (or moldings) obtainable from the casting resins, and the use of such shaped bodies.

[0002] Such casting resins are known in principle, in particular as epoxy resins for potting (Verguβ, or potting, encapsulation) of electrical or electronic components. Medium- and highly-filled epoxy-based casting resins for heat-cured electrical potting, which cure in a temperature range of 80° C. to 200° C., usually have liquid components that are correctly mixed in terms of reaction stoichiometry, which include diepoxy resins, curing agents, toughening agents, accelerators and additives. For this purpose, microfillers with a particle size in the range of 1-800 μm are preferably introduced. These microfillers are usually silicon oxide and / or aluminum oxide. Since cured, medium- and highly-filled resin moldings are considered to be brittle, non-ductile materials, which have only few or no linear elastic properties, toughening agents are often added to the formulation in a not negligible proportion of 4-20 parts by weight per 100 parts of resin, based on the resin matrix without fillers, in order to improve the fracture mechanical properties of the material. Tougheners commonly used for electrical potting are based on polyethylene glycol or polypropylene glycol with a molecular weight of up to 500 Daltons that are liquid at room temperature. Due to their flexible polyether structure, they produce a certain ductility in the polymer network after polymerization, thereby inhibiting crack initiation and crack growth (propagation), especially for large-volume components.

[0003] However, a serious disadvantage of introducing toughening agents is the simultaneous decrease in the glass transition temperature of the resulting material. Even the addition of relatively small amounts of about 2% by weight of polypropylene glycol-400 to a microfiller-free epoxy resin base matrix made of bisphenol diglycidyl ether, phthalic anhydride derivatives and amine accelerators already shows a 10-15°C decrease in the glass transition temperature at generally the same final curing temperature.

[0004] The glass transition temperature ("Tg") usually determines the maximum operating temperature of electrical materials, since thermal overshoots caused by heating, for example at hot spots, etc., lead to dimensional instabilities, accelerated electrical and mechanical aging and ultimately to component failures. In switchgear in particular, a glass transition temperature above the continuous operating temperature is therefore required. The continuous operating temperature below the glass transition temperature of the epoxy resin molding material used is also determined in part by the standardization of the permissible rated current.

[0005] Therefore, a decrease in the material glass transition temperature of casting resins for electrical potting is not economically feasible. Instead, the aim is in principle to increase the glass transition temperature while maintaining all other relevant process and material parameters.

[0006] The present invention relates to the following tensio-dynamic area: on the one hand, the rheological properties of the formulation for processing are maintained, while on the other hand, the glass transition temperature of the cured molding is increased. In this context, a maximum dynamic viscosity of 26 Pa·s, preferably a maximum of 12 Pa·s, at a shear rate of 0.1-100 1 / s, for example, is regarded as the rheologically useful behavior of the casting resin.

[0007] The object of the present invention is therefore to create a formulation for casting resins by which the following two properties can be achieved: the glass transition temperature or the glass transition region of the finished molding is increased and at the same time the crack resistance is increased compared to conventional casting resins with up to 20 parts by weight of toughening agents, with approximately the same rheological behavior and otherwise approximately unchanged process and material parameters.

[0008] This object is achieved by the subject matter of the invention disclosed in the description and the claims.

[0009] Therefore, a first solution to the object and subject of the invention is a casting resin which comprises at least components A and C, wherein - in the case of addition polymerization - component A still contains a curing agent component B in the casting resin, and

[0010] -A is an epoxy resin mixture comprising

[0011] - Between 80 and 95% by weight of diglycidyl ether epoxy resin

[0012] - 1 to 15% by weight of a cycloaliphatic epoxy resin, and

[0013] - 0.1 to 10% by weight of polymer nanoparticles,

[0014] - B is a curing agent, the amount of which has a stoichiometric reaction ratio to component A, and B comprises at least one compound such as an anhydride, an acid anhydride and / or an acid anhydride derivative, in particular phthalic anhydride and / or a phthalic anhydride derivative,

[0015] and

[0016] As component C, a curing catalyst is present in an amount of 0.1 to 20% by weight, based on the amount of liquid casting resin.

[0017] The general understanding of the present invention is that a reduction in the weight fraction of toughening agents in unfilled casting resins or the complete absence of toughening agents leads to an increase in the glass transition temperature or glass transition region of the fully cured molding, but an increase in the viscosity of the casting resin and a decrease in the elongation at break of the cured material. In order to compensate for these disadvantages, it has proven suitable to use an epoxy resin in which polymer nanoparticles are distributed in a highly dispersed and suspension-stable manner together with, i.e., in combination with, a mixture of this epoxy resin and a certain proportion of a cycloaliphatic epoxy resin.

[0018] Scanning electron images of the fracture surfaces without filler and with filler can be used to detect the contained highly dispersed nanoparticles, these can be identified from the scanning electron images, see M. Thesis in Erlangen, 2010.

[0019] The casting resin according to the invention and defined above in the form of a liquid resin mixture having components A and C and—depending on the polymerization mechanism—component B can be filled with additives and / or microfillers like conventional casting resins.

[0020] The microfillers are preferably in the form of spherical and / or angular particles having a particle size in the range from 0.1 μm to 1000 μm. The microfillers are in particular mineral compounds, such as metal oxides, generally nitrides, for example boron nitride and / or silicon dioxide in various modified forms.

[0021] For example, a toughening agent based on polyethylene glycol and / or polypropylene glycol having a molecular weight of up to 500 Daltons which is liquid at room temperature can also be added to the liquid resin component in an amount of less than 20 parts by weight, in particular less than 10 parts by weight, preferably less than 5 parts by weight. However, the amount thereof is particularly preferably small or even absent.

[0022] The omission of tougheners in conventional formulations of epoxy resin / anhydride mixtures adjusted to the correct reaction stoichiometry for casting resins always leads to an increase in the glass transition temperature compared to formulations containing tougheners, but at the same time a reduction in the elongation at break, the fracture toughness and / or the corresponding critical fracture energy, so that the material breaks more easily and is also significantly more brittle. This can be seen from the reduction in the elongation at break of the molding material and the reduction in the fracture toughness of the formulations now without tougheners and the lack of ductile regions in the polymer network (which, for example, is caused by long-chain tougheners).

[0023] The fracture toughness Kc can be expressed, for example, in the fracture mechanical tensile / bending load case "I" as K IC (Unit: MPa·m 1 / 2 ) indicates that the fracture toughness Kc can be increased by increasing the microfiller content, but at the same time the corresponding critical fracture energy G ICdecreases, since this is inversely proportional to the elastic modulus E. This means that, although the stress rise required at the crack tip until catastrophic fracture increases due to the increase in filler content, the energy required for the creation of a new surface in the cracked component at the moment of fracture decreases. Therefore, if Kc and Gc increase simultaneously, the material is less sensitive to crack initiation and / or crack propagation. Therefore, an increase in the glass transition temperature with a simultaneous embrittlement of the material, i.e. a decrease in the material's elongation at fracture without an increase in the mechanical parameters of fracture, always leads to a less elastic component, despite the increase in the glass transition temperature.

[0024] Thus, increasing the glass transition temperature of the material by reducing the proportion of toughening agents or even completely excluding toughening agents can overcompensate with the material itself leading to ductile polymer regions to maintain the processability and fracture mechanical properties of the molded body made of the casting resin without reducing the glass transition temperature.

[0025] According to the invention, this is achieved by adding a cycloaliphatic epoxy resin and simultaneously introducing "soft" nanoparticles. Preferably, polymer nanoparticles are introduced, in particular polymeric, rubbery nanoparticles, for example made of styrene-butadiene rubber or polybutadiene rubber (Kautschuk) and / or gum (Gummi), which may include various copolymers, blends and / or mixtures.

[0026] Here, the difference between blends, polymer blends and copolymers is that polymer blends are true mixtures, that is, there are no covalent chemical bonds between the individual monomers, but at most hydrogen bonds, van der Waals attractions, etc. exist.

[0027] "Soft" nanoparticles preferably include elastomers, rubbers and / or gums. In order to use in a resin matrix, this nanoparticle is also preferably coated with a coating, which promotes incorporation, distribution and therefore dilution into the resin matrix. For example, the particle includes a rubbery polymer, blend and / or a copolymer, such as those that can be obtained from for example butadiene, vinylbenzene, siloxane and / or acrylic monomers.

[0028] For example, so-called core-shell rubber CSR particles can advantageously be introduced into the casting resin.

[0029] These are nanoparticles with a soft, polymeric, rubbery core which have a shell, for example in the form of a coating. The coating is particularly suitable for preventing the nanoparticles from agglomerating in the resin matrix. Such CSR particles are commercially available and are already available, for example, from the company Kaneka under the trade name Ace TM MX is available as a mixture with various epoxy resins, including cycloaliphatic epoxy resins.

[0030] In particular, diglycidyl ether epoxy resins known for this application have proven to be useful as "epoxide-based resins".

[0031] Surprisingly, it has been shown here that relatively high glass transition temperatures can be achieved in epoxy resin-anhydride derivative mixtures or anhydride-free diglycidyl ether-epoxy resin mixtures without large amounts of toughening agents when epoxy resins based on diglycidyl ethers are mixed with cycloaliphatic epoxy resins and dispersed, preferably highly dispersed, polymer nanoparticles.

[0032] As cycloaliphatic epoxy resins suitable for mixing with the diglycidyl ethers there are found those of the cycloaliphatic diepoxy resin type, in particular those of the 3,4-epoxycyclohexylalkyl-3′,4′-epoxycyclohexanecarboxylate and / or bis(3,4-epoxycyclohexylalkyl)-adipate type, where for example alkyl=methyl, ethyl.

[0033] These cycloaliphatic diepoxy resins are preferably low-viscosity and are therefore preferably halogen-free, in particular chlorine-free.

[0034] The low viscosity of the cycloaliphatic epoxy resin reduces the overall viscosity of the liquid component, so the casting resin can copolymerize well with the curing agent such as anhydride.

[0035] With the mixture of the highly dispersed polymer nanoparticles proposed according to the invention in an amount of 0.1 to 10% by weight (based on component A of the casting resin), a low-viscosity prepolymer which is heat curable is obtained.

[0036] The present invention is explained in more detail below with the aid of examples:

[0037] The casting resin according to an embodiment of the present invention comprises in the casting resin component A 80 to 95 wt %, preferably 87.5 to 92.5 wt %, particularly preferably 89 to 91 wt % of diglycidyl ether epoxy resin; 1 to 15 wt %, preferably 2.5 to 10 wt %, particularly preferably 4 to 8 wt % of alicyclic epoxy resin; and 0.1 to 10 wt %, preferably 0.5 to 7.5 wt %, particularly preferably 1 to 5 wt % of polymer dispersed nanoparticles.

[0038] These three components then add up to 100% by weight of the casting resin, resin base component A.

[0039] In component A, the diglycidyl ether epoxy resins are present, for example, bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, epoxy phenol novolacs and / or epoxy phenol novolacs in which the repeating unit n is in the range of 0≤n≤0.2. For this purpose, in the case of addition polymerization, an anhydride is added as curing agent component B, for example, methyltetrahydrophthalic anhydride and / or one or more structural isomers thereof, such as are known under the CAS numbers 11070-44-3 and 26590-20-5, for example, also hexahydrophthalic anhydride, methylnadic anhydride or any other monofunctional carboxylic anhydride which is liquid at room temperature and / or a difunctional or higher-functional carboxylic anhydride which is solid at room temperature, but preferably methylhexahydrophthalic anhydride, for example, as the product Aradur HY 918 from Huntsman. Component B is added in 80 to 90 parts by mass, in particular in 80 to 85 parts by mass.

[0040] Component C, the curing accelerator, is, for example, a tertiary amine, preferably one with a low vapor pressure at room temperature, such as dimethylbenzylamine, dibenzylmethylamine, 1,2-dialkylimidazoles, such as 1-decyl-2-methylimidazole. For example, the compound "Accelerator DY062" from Huntsman is used for this purpose.

[0041] Component C is present in an amount of 0.1 to 10% by weight, in particular 0.5 to 5% by weight and preferably 1 to 2.5% by weight in the case of addition polymerization, based on the curing agent component B. In the case of homopolymerization, the weight ratio of component A to component C is, for example, 100:20, in particular 100:10, particularly preferably 100:5, the lower ratios relating to component C in each case.

[0042] Both components A and B may be filled with microfillers. The microfillers are present in an amount of 50% to 85% by weight, in particular 55% to 80% by weight, in particular 57% to 78% by weight, based on the casting resin.

[0043] It has been shown that dispersed nanoparticles with an average particle size of less than 200 nm lead to a reduction in the overall viscosity in a casting resin mixed with a microfiller whose smallest particle is greater than or equal to 150 nm. This is due to the ball bearing effect of the polymer nanoparticles between the significantly larger microfiller particles. The average particle size of the microfiller particles, which may be present in one or more fractions, is in the range of 0.1 μm to 1000 μm.

[0044] The microfiller is preferably a metal oxide and / or silicon dioxide. In addition to crystalline, spherical and / or angular quartz powder, amorphous quartz products, spherical and / or angular alumina, aluminum hydroxide (ATH), dolomite and / or spherical boron nitride with similar particle size distribution characteristics, and any mixture of the above substances can also be considered as the target microfiller.

[0045] As an example of the present invention, a premix of three casting resin components A, B and C was performed, wherein A=comprises BADGE (Huntsman Araldite CY 228), ECC (e.g., Huntsman Araldite CY 179), and MX (Kaneka ACE MX-154). The commercially available Kaneka ACE MX-154 component can be used as a 40% concentration nanoparticle dispersion in a commercially available bisphenol A-diglycidyl ether resin (i.e., such as BADGE).

[0046] The alicyclic epoxy resin ECC has strong fluidity and is distributed in the mixture in a stable manner without phase separation. After the epoxy resin components of the three epoxy resins are mixed evenly, they exhibit slightly opaque yellow, translucent uniformity and easy mobility at room temperature.

[0047] The casting resin mixture exemplified herein for the present invention comprises 80 to 90 parts by mass of BADGE, 7 to 15 parts by mass of Kaneka Ace MX-154, which contains polymer dispersed nanoparticles, and 2 to 7 parts by mass of Kaneka Ace MX-154 alicyclic epoxy resin Araldite CY 179, and can be used as epoxy resin component A in the casting resin.

[0048] As a comparative example of the prior art, a base casting resin material which can be thermally cured by 1.5 parts by mass of a tertiary amine ("ACC", benzyldimethylamine, Huntsman DY062) was used.

[0049] A = 100 parts by mass of reactive diluted bisphenol A-diglycidyl ether epoxy resin ("BADGE"),

[0050] B = 82.5 parts by mass of methyltetrahydrophthalic anhydride ("MTHPA") as a curing agent, 4 parts of polypropylene glycol-400 as a toughening agent ("FLEX") and

[0051] 368 parts of quartz powder filler fraction (= 66.2 wt%) dispersed therein, with an average particle size of about 20 pm (D 50 Values, determined by dynamic light scattering DLS in aqueous dispersions; Malvern Mastersizer 2000).

[0052] The glass transition temperature of a casting resin according to the prior art which is cured at 140° C. for 10 hours is about 105-107° C. according to the DSC method (10 K / min, determined using the half-height method).

[0053] Its filler-free base resin mixture according to the prior art (also referred to as "original" in the table) has been modified while maintaining / improving all other properties according to the invention in such a way that

[0054] 1) Tougheners are omitted and replaced sequentially with increasing proportions of cycloaliphatic epoxy resin ("ECC"), while

[0055] 2) The first 100 parts of the base epoxy resin were sequentially stretched with a 40% concentration of a highly dispersed masterbatch rich in nanoparticles (Kaneka Ace MX 154 or Kaneka Ace MX 150).

[0056] For the glass transition temperature, the following results were obtained using the above-mentioned DSC method from the following mixtures in parts by mass [MT]:

[0057] 1) Reference sample "original"

[0058] 100 MT BADGE:82.5 MT MTHPA:4 MT FLEX:1.5 MT ACC:

[0059] The glass transition temperature is 107°C

[0060] 2) Sample A—Exemplary embodiment of the present invention

[0061] 87 MT BADGE:82.5 MT MTHPA:17 MT MX-Harz:1.5 MT ACC:

[0062] Glass transition temperature is 111°C ("A")

[0063] 3) Sample B—Exemplary embodiment of the present invention

[0064] 87 MT BADGE:82.5 MT MTHPA:13 MT MX-Harz:4 MT ECC:1.5 MT ACC:

[0065] Glass transition temperature is 117°C ("B")

[0066] 4) Sample C—Exemplary embodiment of the present invention

[0067] 87 MT BADGE:82.5 MT MTHPA:12 MT MX-Harz:5 MT ECC:1.5 MT ACC:

[0068] The glass transition temperature is 123°C.

[0069] It is shown that even with a relatively low proportion of cycloaliphatic epoxy resin (ECC) and omitting the toughening agent (FLEX), a glass transition temperature of more than 120°C can be achieved in the mixture "C" compared to the mixture "original". It should be noted that the nanoparticle-rich resin (MX, such as Kaneka Ace MX type) with a 40% dispersed distribution of nanoparticles with a particle size of 80-200 nm also introduces particles into the modified resin mixture. This can be seen from the opaque appearance of the mixture "A" without microfiller to "C", which is caused by the refraction of light by the nanoparticles. Therefore, the mixture "C" without filler is suitable as a casting resin mixture in terms of glass transition.

[0070] According to an advantageous embodiment, the microfiller, for example in the form of a quartz powder filler, is optimized in terms of its packing density. Here, the packing factor can be increased by about 2 to 7% by volume, in particular by 3.5 to 5% by volume. Casting resin "C" is loaded with 71.1% by weight or 52.3% by volume of the microfiller Silbond 126, wherein in addition about 2.8% by weight or 2.5% by volume of polymer nanoparticles are added to the microfiller-free casting resin via resin MX. Overall, this corresponds to a filler loading of 73.9% by weight or 54.8% by volume. The polymer nanoparticles act as an efficient rheological additive in the casting resin, since an additional increase in packing density is also achieved by these particles, and the fluidity of the casting resin is significantly increased again. Thus, the formulation shows a maximum viscosity of only about 11000-12500 m·Pas at a shear rate of about 1 1 / s at 50° C., despite the fact that more than 8% by volume of the total filler is effectively dispersed.

[0071] In addition, the dynamic viscosity at very low shear rates of around 0.01 1 / s at 50°C is particularly low, at about 3000 mPa·s, which is particularly advantageous for the automatic closing of voids (pores) in static tools during potting when the material is at rest after the filling process and is ready for thermal curing. All these factors are reflected in the cured moldings in the form of significantly improved characteristic parameters (or so-called characteristic values). The mechanical and fracture mechanical parameters were determined at room temperature according to the three-point bending test or double torsion geometry. The glass transition temperature was determined by differential calorimetry and thermomechanical analysis (TA Instruments DSC, 10 K / min and TMA, 3 K / min). The specific density was determined at room temperature using the buoyancy method and helium manometry, and the thermal conductivity was determined using the laser flash method or laser flash analysis - LFA. The gel time of the resin mixture without filler was determined according to Gelnorm. A comparison of the relevant characteristic values ​​of "original" and sample "C" is shown in Table 1 below.

[0072] 70-90 parts by weight of BADGE and 30-10 parts by weight of 30-40% concentration of MX resin from Kaneka (e.g. Kaneka Kane ACE TM Mixtures of MX 120, 125, 135, 136, 150, 153, 154, 156, 170, 217, 257, 267, 553, 960) - in a stoichiometrically correct mixture with anhydride curing agents and curing catalysts based on tertiary amines - have shown very good rheological properties of the casting materials and very good properties of the moldings obtained by thermal curing from the above-mentioned casting resins C. All mechanical, fracture mechanical and thermomechanical parameters measured on this material are superior to the prior art, so that a material which is very suitable for electrical potting is obtained.

[0073] The gel time is also considered to be the same and allows for the same curing and gelling conditions as with prior art resins and known manufacturing processes, ie for example in vacuum potting and automated pressure gelling processes (ADG).

[0074] In summary, sample C has the following characteristic value changes compared with conventional products:

[0075] 1. The maximum dynamic viscosity of the casting resin is reduced by more than 30%,

[0076] 2. Will not prolong or shorten the gelling behavior at high temperature,

[0077] 3. The elastic modulus only increased by 11%,

[0078] 4. Flexural strength increased by 4%,

[0079] 5. The elongation at break is only reduced by 4%.

[0080] 6. Fracture toughness K IC Increase by 24% or 38% (critical fracture energy G IC ),

[0081] 7. The glass transition temperature is increased to above 120°C.

[0082] 8. Thermal expansion reduced by 7%,

[0083] 9. Thermal conductivity increased by 12%.

[0084]

[0085] a According to DIN53452 or in accordance with DIN EN ISO 178

[0086] b According to ASTM E 399-09 or ASTM D5045-99

[0087] c According to ASTM ISO 11359-2

[0088] d According to DIN 16945, DIN 16916 or EN 14022

[0089] e According to ASTM E1461 or EN821

[0090] Since nanoparticle masterbatches such as Kaneka Kane Ace TM MX-154 and / or all other commercially available Kane Ace TM MX types contain polymer nanoparticles in highly dispersed and completely depolymerized form, so that in this case there is no inhalable and therefore dangerous dry nanoparticle dust. For example, no isolated nanoparticles were found in the sawdust of the material obtained according to sample C, since these nanoparticles were embedded in the epoxy resin matrix and remained embedded, as can be demonstrated by Malvern Nanosizer analysis.

[0091] The shaped bodies produced from the casting resin according to the invention can be used for electrically stressed components, in particular switchgear components, cast-resin transformers, coils and the like.

[0092] A portion of the surface treated microfillers can also be present as microfillers in the casting resin. For example, surface silanized microfillers such as Silbond W12EST or Silbond 126EST have proven to be suitable.

[0093] The present invention proposes for the first time a casting resin for heat-cured electrical potting in which plasticizers and tougheners can be omitted. This is achieved by mixing an epoxy resin base with a cycloaliphatic epoxy resin and adding highly dispersed nanoparticles.

[0094] The invention can be verified by identifying nanoparticles and cycloaliphatic modified casting resins based on epoxy resin bases. If this is not possible, evidence can be provided by analyzing the material, for example by scanning electron images of fracture surfaces, on which fine distribution, i.e. nanoparticles present in a dispersed manner, can be distinguished.

[0095] In addition, ATR-IR analysis can be used to detect alicyclic infrared oscillations in the high-wave range due to their nonaromatic nature. In addition, the nanoparticles can be dissolved and leached on the sawn surface with methanol. Since the cured epoxy resin is insoluble in methanol, the hollow hemispheres will remain on the sawn / fractured surface.

Claims

1. A casting resin comprising at least components A and C, wherein: In the case of addition polymerization, component A is still present in the casting resin as a hardener component B, and -A is an epoxy resin mixture comprising - Between 80 and 95% by weight of diglycidyl ether epoxy resin - 4 to 8% by weight of a cycloaliphatic epoxy resin, and 0.1 to 10% by weight of polymer nanoparticles having an average particle size of less than 200 nm, said nanoparticles having a core of a rubbery polymer and a shell in the form of a coating, wherein said shell prevents the nanoparticles from agglomerating in the resin matrix, - B is a curing agent, the amount of which has a reaction stoichiometric ratio to component A, and B is phthalic anhydride and / or a phthalic anhydride derivative, and - as component C, a curing catalyst is present in an amount of 0.1 to 20% by weight, based on the amount of liquid casting resin, wherein in addition to the nanoparticles one or at least two microfiller fractions are present in the casting resin, and wherein the at least one diglycidyl ether epoxy resin of component A is bisphenol A-diglycidyl ether, and the alicyclic epoxy resin of component A is selected from the following compounds: alicyclic diepoxy resins of the type of 3,4-epoxycyclohexylalkyl-3',4'-epoxycyclohexanecarboxylate and / or bis(3,4-epoxycyclohexylalkyl)-adipate, wherein the alkyl group = methyl and / or ethyl, and any copolymers and / or mixtures of the above alicyclic epoxy resins, The polymer nanoparticles of component A are present in rubbery form, wherein the nanoparticles comprise a core made from a polymer made from butadiene, styrene, siloxane and / or acrylic monomers and wherein the partially coated nanoparticles are present as core-shell rubber CSR particles.

2. The casting resin according to claim 1, wherein the nanoparticles are present in an average particle size in the range of 80 to 200 nm.

3. A casting resin according to claim 1 or 2, wherein the nanoparticles are present in dispersed form.

4. A casting resin according to claim 1 or 2, wherein dispersed nanoparticles are present in the epoxy resin mixture. 5 . The casting resin according to claim 1 , wherein the nanoparticles are present in component A in an amount of 0.5 to 7.5% by weight, based on the total weight of component A.

6. Casting resin according to claim 1 or 2, wherein the microfiller is present in an amount of 50 to 98% by weight, based on the total casting resin.

7. The casting resin according to claim 1 or 2, wherein the microfiller does not include an average particle size d 50 Particles less than or equal to 300nm.

8. The casting resin according to claim 1 or 2, wherein the microfiller does not include an average particle size d 50 Particles less than or equal to 150nm.

9. Moulded body obtainable by curing a casting resin according to any one of claims 1 to 8.

10. Use of the shaped body according to claim 9 in electrical components.

11. Use of the shaped body according to claim 9 in components of switchgear.

12. Use of the shaped body according to claim 9 in cast resin transformers and / or coils.

Citation Information

Patent Citations

  • Heat-resistant drip-feed impregnating resin

    JP1996113697A

  • Casting resin composition for insulation for electrical equipment

    JP1999035805A

  • Epoxy resin composition for fiber-reinforced composite material

    JP2018035210A

Cited By

  • Casting molding method for resin handicrafts by using waste high polymer materials

    CN120829659A

  • Resin art casting method using waste polymer materials

    CN120829659B